Insight into in-situ modification of white carbon black with surfactant/silane coupling agent via surface grafting and its performance - Shenxu Bao; Bo Chen; Shun Wang (Mongolian Geoscientist)
Hydrophobic and highly dispersed modified white carbon black particles were prepared using surfactant sodium dodecyl sulfate as a modifier and the vanadium-extraction residue as raw material. This study investigated the effects of modification temperature, pH value, aging time and dosage of modifier. In order to reflect the advantages of surfactant sodium dodecyl sulfate modification, the silane coupling agent γ-methacryloxypropyl trimethoxysilane was used to compare with it. The modified white carbon black prepared by in-situ grafting method with sodium dodecyl sulfate and γ-methacryloxypropyl trimethoxysilane was compared. X-ray diffraction and fourier transform infrared spectrometer results indicate that the modified product has an amorphous structure and the modifier exists on the surface of white carbon black in the form of chemical grafting. The modified product is added as fillers to rubber and the mechanical properties of rubber show that the white carbon black modified by sodium dodecyl sulfate has a lower modulus of elasticity, a higher maximum tensile stress and the strain at yield. The results of scanning electron microscope images of rubber and particle size of modified white carbon black demonstrate that the fine-grained modified white carbon black particles are more likely to form a network structure with the rubber to enhance the mechanical properties of the rubber.